Organizational Support and Career Development on Organizational Commitment: A Study in the Financial Services Industry in Indonesia - Sinaga, Herty Ramayanti; Khuan, Hendri; Supardi, Supardi; Irdhayanti, Efa (International Journal of Business, Law, and Education, 2024)
This study investigates the interplay between organizational support, career development, and organizational commitment within the financial services industry in Indonesia. The research aims to shed light on how these factors influence employee engagement and retention in a rapidly evolving sector crucial to Indonesia's economic growth. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data was collected from employees across various roles in financial organizations. The analysis revealed significant positive relationships between organizational support and organizational commitment, career development and organizational commitment, as well as the sequential effect of organizational support on career development, leading to organizational commitment. These findings highlight the importance of fostering supportive environments and providing growth opportunities to enhance organizational commitment. The study suggests that prioritizing initiatives that promote organizational support and career development can lead to a more engaged and committed workforce, ultimately improving organizational performance and competitiveness in the financial services sector in Indonesia.